The Role of Time Driven Activity Based Costing (TDABC) in Determining the Cost of Unutilized Resources - Case Study on the Faculty of Commerce - Al-Zaytoonah University (Economic studies journal, 2025)
The study aimed to identify the role of the time-driven activity-based costing (TDABC) system in determining the percentage of utilized and unused energy, and determining the cost of unused resources at the Faculty of Commerce at Al-Zaytouna University - Libya, where the researcher conducted an applied study on the Faculty of Commerce to reach the desired result. The study concluded that the utilized energy amounted to (588160) minutes, and its cost was (247027) dinars, while the unused "idle" energy was (3629696) minutes, and its cost was (1547641) dinars, so that the percentage of utilized energy in the college amounted to (14%), and the percentage of unused energy in the college was (86%). The researcher recommends that the college administration try to utilize the college's resources to the maximum extent, so that the gap between utilized and unused energy is reduced.
Keywords: Time-Driven Activity-Based Costing; Cost Accounting (TDABC); Planned Capacity; Utilized Capacity; Idle Capacity